The Influence of Factors Affecting the Willingness to Pay for Reduction of Air Pollution in Zimmerman - Mugo, Gathogo Daniel; Mutsembi, Mr. Manundu; Dr. Wafula, Masai (International Journal of Environmental Sciences, 2016)
Purpose: The purpose of this study was to identify the factors that determine the willingness to pay for reduction in air pollution in Zimmerman. Methodology: System random sampling was used to select the sample of the study. The sample size was limited to 150 households. Ordinary least squares technique was applied in the data analysis to investigate the influence of the identified explanatory variables on the willingness to pay. Results: The study results showed that the size of household, age, marital status of respondent and incidence of a polluted illness in a respondent's household are related to the willingness to pay for reduction in air pollution although they are insignificant at the 95 percent level of significance. Unique contribution to theory, practice and policy: The study recommended that increasing the income of the individuals may lead to an increase in the charges for air pollution abatement. Educating the people about the virtues of a pollution free environment may increase their willingness to pay for air pollution reduction via payment vehicle such as taxes and service charges or higher prices. The government can help reduce the housing problem by solving the air pollution problem which will further encourage investments in residential housing units in the undeveloped parts of Zimmerman given that it is an important residential estate for the lower middle class to the upper middle class groups as evidenced from the income data gathered.